Recent advancements in the diagnosis and treatment of congestive heart failure in dogs and cats - Ward, Jessica (Henry Stewart Talks, 2018)
Diagnosis and treatment of CHF in dogs and cats, Recent trends in CHF management, NT-proBNP for diagnosis of CHF in cats, Lung ultrasound for diagnosis of CHF, Pimobendan dose escalation for dogs with chronic CHF, Pimobendan for cats with CHF, Spironolactone as standard treatment for chronic CHF in dogs, Sildenafil in dogs with CHF and pulmonary hypertension